Rattus korinchi - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
081. Sumatran Mountain Rat Rattus korinchi French: Rat du Kerinci / German: Sumatra-Ratte / Spanish: Rata de montana de Sumatra Other common names: Kerinci Rat, Korinch’'s Rat Taxonomy. Epimys korinchi H. C. Robinson & Kloss, 1916, Sungai Kring, 7300 ft (= 2225 m), Gunung Kerinci, Propinsi Jambi, western Sumatra, Indonesia. Phylogenetic position of R. korinchi inRattus is unclear, although it might be related to R.baluensis, which it has been considered conspecific with. Monotypic. Distribution. Mt Talakmau and Mt Kerinci, W Sumatra. Descriptive notes. Head-body 166- 169 mm, tail 209-224 mm, ear 23 mm, hindfoot 34-35 mm. No specific data are available for body weight. The Sumatran Mountain Rat is medium-sized, with long, dense, and soft pelage. Dorsum is dark tawny, with longer black guard hairs mixed throughout and slightly lighter on sides. Hairs are gray-tipped, with ocherous tawny bases. Venter is grayish white, with white patches on throat, chest, and inguinal region, and not sharply demarcated from dorsum. Feet are brown, with darker brown stripe down each metatarsal and metacarpal, and claws are sharp, recurved, and short. Ears are small, brown, and covered with short brown hair. Tail is ¢.125-135% of head-body length, and unicolored brown, covered in dark brown hair and brown and silver hairs that extend past tail tip. Skull is moderately large, with squarish braincase and slender rostrum. There are three pairs of mammae: one pectoral and two inguinal. Habitat. Primary upper montane or moss forests. Food and Feeding. No information. Breeding. No information. Activity patterns. No information. Movements, Home range and Social organization. No information. Status and Conservation. Classified as Data Deficient on The IUCN Red List. There is virtually nothing known about the Sumatran Mountain Rat, and studies are required to fully understand it natural history, taxonomy, and threats. It does not seem to have any major threats other than distributional restriction due to habitat loss in lowland areas ...